Persistence in the Realized Betas: Some Evidence for the Spanish Stock Market - Guglielmo Maria Caporale; Luis A. Gil-Alana; Miguel Martin-Valmayor (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper examines the stochastic behaviour of the realized betas within the one-factor CAPM for the six companies with the highest market capitalization included in the Spanish IBEX stock market index. Fractional integration methods are applied to estimate their degree of persistence at the daily, weekly and monthly frequency over the period 1 January 2000 – 15 November 2018 using 1, 3 and 5-year samples. On the whole, the results indicate that the realized betas are highly persistent and do not exhibit mean-reverting behaviour. However, the findings are rather sensitive to the choice of frequency and time span (number of observations).
Keywords: C22; G11; 330; realized beta; CAPM; persistence; mean reversion; long memory